PENGALAMAN PEMASARAN DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN DAN KEPERCAYAAN SEBAGAI VARIABEL MEDIASI - Kevin Benitto Hartono; Lina Salim (Fakultas Ekonomi Universitas Pekalongan, 2020)
Nowadays, shopping malls growth are extremely high in Jakarta area. One of the shopping malls that has existed for a long time and still thrives in Jakarta is Mal Kelapa Gading (MKG). The objective of this research is to examine the impact of experiential marketing and service quality toward MKG’s customer loyalty with customer satisfaction and trust as mediation variables. The data was collected by distributing 233 questionnaires to the residents around the area of the mall. As this research model has passed 11 goodness of fit test indicators, this model has been proven consistent to the empirical data. There are 6 hypotheses in this research, 4 of which are proven true. The results of this research indicate that there is a positive impact in experiential marketing and service quality toward customer loyalty with customer satisfaction and trust as mediation variables. On the one hand, customer satisfaction has become the best mediating variable to strengthen the impact of experiential marketing and service quality toward customer loyalty. On the other hand, experiential marketing and service quality do not affect trust. Trust is useful as a mediating variable if there is an influence from customer satisfaction. Keywords: Consumers’ Satisfaction, Customers’ Loyalty, Experiential Marketing, Service Quality, Trust